Role of the proteasome and NF-κB in streptococcal cell wall-induced polyarthritis - Palombella, Vito J. (The National Academy of Sciences, 1998)
The transcription factor NF-κB activates a number of genes whose protein products are proinflammatory. In quiescent cells, NF-κB exists in a latent form and is activated via a signal-dependent proteolytic mechanism in which the inhibitory protein IκB is degraded by the ubiquitin–proteasome pathway. Consequently, inhibition of the proteasome suppresses activation of NF-κB. This suppression should therefore decrease transcription of many genes encoding proinflammatory proteins and should ultimately have an anti-inflammatory effect. To this end, a series of peptide boronic acid inhibitors of the proteasome, exemplified herein by PS-341, were developed. The proteasome is the large multimeric protease that catalyzes the final proteolytic step of the ubiquitin–proteasome pathway. PS-341, a potent, competitive inhibitor of the proteasome, readily entered cells and inhibited the activation of NF-κB and the subsequent transcription of genes that are regulated by NF-κB. Significantly, PS-341 displayed similar effects in vivo. Oral administration of PS-341 had anti-inflammatory effects in a model of Streptococcal cell wall-induced polyarthritis and liver inflammation in rats. The attenuation of inflammation in this model was associated with an inhibition of IκBα degradation and NF-κB-dependent gene expression. These experiments clearly demonstrate that the ubiquitin–proteasome pathway and NF-κB play important roles in regulating chronic inflammation and that, as predicted, proteasome inhibition has an anti-inflammatory effect.